Medication-related osteonecrosis of the jaw as a complication of palliative treatment of breast cancer - Janik, Katarzyna; Wziątek-Kuczmik, Daria; Galicka, Zuzanna; Kamiński, Maciej; Niedzielska, Iwona (Medycyna Paliatywna/Palliative Medicine, 2025)
Medication-related osteonecrosis of the jaw (MRONJ) is a disease associated with the dysregulation of bone metabolism due to antiresorptive or antiangiogenic therapy. Any surgical interventions at such a stage should be performed under antibiotic cover. This report describes a case of a patient who underwent oral surgery without antibiotic cover, while receiving intravenous zoledronate treatment, which led to the development of MRONJ. Initially, her state corresponded to stage 2 of the disease. At that moment, the patient refused to continue the recommended surgical treatment. One year later she was referred to the clinic due to mobility of the mandible, which corresponded to stage 3 of MRONJ. A segmental resection of the mandible, followed by reconstruction using a titanium plate, was performed. This case highlights the importance of interdisciplinary collaboration between different specialists, as well as clear communication with the patient during the diagnostic process and treatment planning.